Study on time–space characteristics of gas drainage in advanced self‐pressure‐relief area of the stope - Xi Jie; Wang Zhaofeng; Chen Dongdong; Chen Jinsheng (Energy Science & Engineering, 2023)
Abstract Gas drainage is an important measure to ensure energy safety in coal mines. However, for mines with high gas content and low permeability, the critical question is how to enhance the drainage effect of drilling. By using the self‐unloading pressure effect on the coal body in front of the mine, the permeability of the coal body can be improved, which facilitates gas drainage. Therefore, establishing the fluid–solid model of gas‐bearing coal mass under the influence of mining, this paper simulates the advanced self‐pressure‐relief range in front of the coal working face and the permeability of coal seam at different heights. Through simulations and field tests, the reasonableness of the advanced self‐pressure‐relief gas drainage was verified, and the spatial and temporal characteristics of the gas drainage from the borehole were quantified and analyzed. The results show that the width of the advanced self‐pressure‐relief zone after simulated mining is 25 m, the vertical permeability of the coal seam increases first and then decreases with the increase of the height from the floor, and the maximum permeability of the layer is 2.6 m from the floor, which is 8.62 times higher than the initial permeability; the gas drainage effect of test boreholes has a periodic law with the coal seam recovery, which, divided into the initial drainage stage, the scalar volume of gas drainage increase stage, and the scalar volume of gas drainage decay stage. At a distance from the working face 20–40 m, the boreholes' scalar volume of gas drainage increased by 3.89 times compared with the initial drainage stage, and the scalar drainage volume of the boreholes through the seam increased by 8.01 times compared with the initial drainage stage; in the section of increasing scalar volume of drainage, the gas drainage volume of the boreholes at different heights of the coal seam had obvious “stratification” phenomenon. The test boreholes were optimally placed in the middle of the seam at the lower end. The study provides a reference for self‐pressure‐relief gas drainage technology and optimization of borehole placement.